Patologi Reformasi Birokrasi Pelayanan Publik Pada Dinas Kepemudaan Dan Olahraga Kota Semarang - Tedo Hindami Guna (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of writing this paper is to study and obtain information on several work relationships in public services and how to overcome these various problems. Bureaucratic Pathology is a disease that eats away at the very foundations of life in a bureaucracy. Bureaucracy is synonymous with the impression of long and convoluted processes, as a result bureaucracy gets a negative image. There are realities experienced in the government bureaucratic environment, such as tortuous work procedures, uneven workload, slow, inefficient, rigid, lack of transparency, corrupt behavior, these conditions are described as sick bureaucracy or bureaucratic pathology. Research is used to determine the conditions and various kinds of bureaucratic pathological practices in Indonesia and how to prevent them in order to create an efficient bureaucracy. The method used in this research is a qualitative approach using literature study techniques. The research results show that the bureaucratic journey in Indonesia is closely related to national culture and is influenced by existing cultural problems. Culture and habits are difficult to change because they are closely related to aspects of morality, this is the beginning of the emergence of symptoms of bureaucratic pathology. The culture of extortion, bribery, slow service, complicated procedures, corruption, collusion and nepotism has become a habit for the Indonesian people. Therefore, efforts that can be made to prevent bureaucratic pathology are by changing the position and role of the bureaucracy that has been implemented so far. Apart from that, applying the principles of good governance can prevent bureaucratic pathology, especially corruption, collusion and nepotism, to create an efficient bureaucracy.